Constrained model assumptions using recent data of α-particle reactions on 144Sm - Avrigeanu, Vlad; Avrigeanu, Marilena (Frontiers in Physics, 2023)
Analysis of the latest high–precision cross sections of (α,γ) and (α,n) reactions on 144Sm below the Coulomb barrier is carried out using a consistent parameter set of the statistical model. This prevents the need to use empirical rescaling factors of either γ or neutron widths. Particular attention is paid to uncertainties of the calculated cross sections which are related to the accuracy of the primary data that were used to set up the consistent input parameters. The calculated cross sections are found in good agreement with the new experimental data for the 144Sm(α,n)147Gd reaction; however, the same is not true for the excitation function of 144Sm(α,γ)148Gd which decreases faster at incident energies below ∼12 MeV. An increase of the α-particle direct collective inelastic scattering at lower energies is found responsible for this decrease of the (α,γ) reaction cross sections. The consequent lower nuclear effects may correspond to the Coulomb excitation effect assumed, although in a different manner, within the so-called “α-potential mystery” for the same optical–potential account of α-particle absorption and emission as well.